Energy-efficient routing for signal detection under the Neyman-Pearson criterion in wireless sensor networks - Yang, Yang; Blum, Rick S. (Proceedings of the 6th international conference on Information processing in sensor networks, 2007)
Energy-efficient routing for wireless sensor networks (WSNs) has been a topic of great interest for the last few years, but thus far routing for signal detection in WSNs has not attracted much attention. In particular, little research has focused on the Neyman-Pearson criterion which is the most well accepted metric for radar, sonar and related signal detection problems. In this paper, we formulate the problem of energy-efficient routing for signal detection under the Neyman-Pearson criterion, apparently for the first time. We hereby propose two different routing metrics that aim at a tradeoff between the detection performance and the energy consumption. In particular, the first one leads to a combinatorial problem of identifying a path which achieves the largest possible mean detection-probability-to-energy ratio, while the second one reduces to finding a route which minimizes the consumed energy while maintaining a predeter-mined detection probability. We further provide efficient algorithms for solving these problems based on state-of-the-art research from operations research. We also present simulation results which indicate the distinctive energy-performance balance achieved by each proposed routing metric.